Rees's manufacturing industry (1819-20) : - Rees, Abraham (David and Charles, 1972)
Abraham Rees's monumental Cyclopaedia, which appeared in parts between 1802 and 1819, was one of the first works of its kind to be published in English which gave more than a passing reference to con-temporary industry and technology. This new printing provides in five volumes, in the original alphabetical form, the articcles on manufacturing industry. This volume covers forty-seven subjects from Acetic Acid to Casting, and includes sections of plates illustrating Bleaching, Canals, Candle, Candle Making, and Casting...